2007
DOI: 10.1590/s1677-04202007000400005
|View full text |Cite
|
Sign up to set email alerts
|

Ecophysiology of tea

Abstract: Tea [Camellia sinensis (L.) O. Kuntze] is one of the most important beverage crops in the world. The major tea-growing regions of the world are South-East Asia and Eastern Africa where it is grown across a wide range of altitudes up to 2200 m a.s.l.. This paper reviews the key physiological processes responsible for yield determination of tea and discusses how these processes are influenced by genotypic and environmental factors. Yield formation of tea is discussed in terms of assimilate supply through photosy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
77
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(88 citation statements)
references
References 86 publications
(188 reference statements)
3
77
0
1
Order By: Relevance
“…De Costa et al (2007) also confirmed greater stomatal densities of the drought susceptible genotypes. However, Chaves (1991) showed that the physiological control of stomatal aperture is more important than the size and frequency of stomata to determine stomatal conductance under water stress.…”
Section: Resultsmentioning
confidence: 53%
“…De Costa et al (2007) also confirmed greater stomatal densities of the drought susceptible genotypes. However, Chaves (1991) showed that the physiological control of stomatal aperture is more important than the size and frequency of stomata to determine stomatal conductance under water stress.…”
Section: Resultsmentioning
confidence: 53%
“…PAR in the chamber was set at a saturating light intensity of 1000 µmol m -2 s -1 (De Costa et al, 2007;2009;Lin et al, 2014;Smith et al, 1993;1994), humidity was maintained above 50 %, to avoid stomatal closure, and leaf temperature was maintained between 28 and 30°C. The CO 2 concentration was adjusted to 400 µmol CO 2 mol -1 with a CO 2 mixer and the air flow was kept constant at 500 µmol s Measurements were performed soon after plucking (0 day), and then 5 and 10 days after plucking at each marked position.…”
Section: Photosynthesis Measurementsmentioning
confidence: 99%
“…In tea, the low yields associated with mechanical harvesting are believed to be compounded by the fact that tea has inherently low productivity (500 -2500 kg ha -1 year -1 of harvested plucked young shoots), which can be partly attributed to harvesting removing much of the active productive leaf area and nutrients (Mohotti & Lawlor, 2002). This is further compounded by inadequate assimilate production (source limitation), as the rates of photosynthesis are low (2-14 µmol m -2 s -1 ) compared to most C3 plants (De Costa et al, 2007;Mohotti et al, 2000;Mohotti & Lawlor, 2002). According to Manivel & Hussain (1982b), plucking results in considerable depletion of dry matter produced by the maintenance leaves in the canopy.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations